Metabolic and Behavioral Effects of Nicotine in Swim Stressed Mice - Bibi, Zehrah; Saeed, Shabana; Bano, Samina (Journal of Pharmacy and Nutrition Sciences, 2022)
Nicotine, in the form of tobacco smoking, is the most commonly abused drug throughout the world. It contributes to the harmful tobacco smoking habit leading to high morbidity and mortality throughout the world. The drug has addictive properties and causes drug dependence. Apart from these effects, nicotine alters a number of metabolic pathways such as lipid profile and glucose homeostasis leading to increased risk of cardiovascular diseases. Present study investigated the metabolic and behavioral effects of nicotine in stressed mice. For this purpose adult male mice were subjected to chronic nicotine treatment(3.08 mg/100 ml in drinking water) for 3 weeks followed by forced swim test (FST) and serum glucose, lipid profile and tryptophan were investigated. When swim stressed mice were compared with chow control, it was found that serum glucose (P<0.001), total cholesterol (P<0.001), triglycerides (P<0.01), and LDL cholesterol (P<0.01) were increased. Similarly glucose concentration (P<0.05), total cholesterol (P<0.05), triglycerides (P<0.01) and LDL cholesterol (P<0.05) were increased in drug treated swim stressed mice. However HDL remained unaltered in both groups. Serum tryptophan was decreased (P<0.01) in swim stressed and nicotine treated swim stressed mice. During FST, swimming behavior was significantly increased at the cost of climbing with no change in immobility in nicotine treated mice as compared to controls. It is concluded that nicotine worsens lipid profile and glucose homeostasis in stressful situations thereby increasing the risk of cardiovascular diseases in chronic smokers and the drug induced behavioral alterations may be related to the serotonergic pathway.